Plaque autoradiography assay for the detection and quantitation of thymidine kinase-deficient and thymidine kinase-altered mutants of herpes simplex virus in clinical isolates. - Martin, J L (1985)
A plaque autoradiography assay to detect and quantitate thymidine kinase (TK) mutants of herpes simplex virus type 1 (HSV-1) and HSV-2 in clinical samples is described. This method utilizes the selective incorporation of [125I]iododeoxycytidine, a pyrimidine analog selectively phosphorylated by the HSV TK. Only cells infected with TK-competent virus will efficiently incorporate iododeoxycytidine and are the only cells detected by autoradiography. Furthermore, this assay discriminates between TK+ virus (TK competent) and TKA virus (TK altered or reduced). This ability to differentiate TK+ from TKA virus is enhanced when infected cells are labeled with [14C]thymidine in tandem with iododeoxycytidine labeling. Reconstruction experiments with mixtures of TK+ (HSV-1 Patton) virus and TK-deficient (TK-) (B2006) or TKA (IUDRr) mutants were performed to determine the limits of detection of this technique. Ten percent TK- or TKA virus was the lower limit for the detection of TK mutants in a mixed population, whereas 1 in 1,000 TK+ virus revertants could be detected in a TK- virus population. In reconstructed populations and 45 clinical samples, a good correlation existed between the increase in 50% inhibitory dose for acyclovir and the percent TK mutant virus present. Similarly, the results of this technique correlated well with the acyclovir phosphorylating activity of extracts from cells infected with isolates or reconstructed mixtures. Plaque autoradiography with [125I]iododeoxycytidine was able to distinguish mixed populations of TK+ and TK- virus and homogeneous populations of TKA virus. The tandem use of [125I]iododeoxycytidine and [14C]thymidine readily identified TKA virus, which appeared as TK+ virus when labeled with [14C]thymidine alone. This technique provides a sensitive screen for antiviral resistance due to alterations in the viral TK and can be used to analyze clinical samples.